2022
DOI: 10.1159/000521331
|View full text |Cite
|
Sign up to set email alerts
|

A Boy with Sandestig-Stefanova Syndrome and Genital Abnormalities

Abstract: <b><i>Introduction:</i></b> Sandestig-Stefanova syndrome is an autosomal recessive developmental syndrome characterized by microcephaly, trigonocephaly, congenital cataracts, microphthalmia, facial findings, camptodactyly, periventricular white matter loss, thin corpus callosum, delayed myelination, and poor prognosis. This syndrome is caused by biallelic loss-of-function mutations in the <i>NUP188</i> gene. <b><i>Case Presentation:</i></b> In the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A recently defined developmental disorder termed Sandestig-Stefanova syndrome (SANDSTEF; MIM 618804) is based upon homozygous and compound heterozygous mutations in NUP188 (Fig. 5; Table 1; [104][105][106]). Patients had pre-and postnatal microcephaly and otherwise strikingly similar clinical features, including premature fusion of the skull (trigonocephaly), vision impairments, facial features, bent fingers (camptodactyly) and rocker-bottom feet, as well as heart and brain anomalies.…”
Section: Developmental Disorders: Microcephalymentioning
confidence: 99%
See 1 more Smart Citation
“…A recently defined developmental disorder termed Sandestig-Stefanova syndrome (SANDSTEF; MIM 618804) is based upon homozygous and compound heterozygous mutations in NUP188 (Fig. 5; Table 1; [104][105][106]). Patients had pre-and postnatal microcephaly and otherwise strikingly similar clinical features, including premature fusion of the skull (trigonocephaly), vision impairments, facial features, bent fingers (camptodactyly) and rocker-bottom feet, as well as heart and brain anomalies.…”
Section: Developmental Disorders: Microcephalymentioning
confidence: 99%
“…Patients had pre-and postnatal microcephaly and otherwise strikingly similar clinical features, including premature fusion of the skull (trigonocephaly), vision impairments, facial features, bent fingers (camptodactyly) and rocker-bottom feet, as well as heart and brain anomalies. Affected children were small at birth and early (infection-associated) respiratory failure led to demise in infancy or early childhood [104][105][106]. The NUP188 protein was undetectable in patient-derived fibroblasts and real-time PCR suggested that the mutant NUP188 alleles are targeted by nonsense-mediated decay.…”
Section: Developmental Disorders: Microcephalymentioning
confidence: 99%